Laboratory and imaging risk factors for mortality in children with primary hemophagocytic lymphohistiocytosis - Huang, Jia; Xu, Sipei; Tang, Rui; Huang, Yan; Li, Wei; Gong, Chundan; Gao, Sijie; Peng, Hailun; Xiao, Li; Ma, Wei (Frontiers in Oncology, 2025)
ObjectivesPrimary hemophagocytic lymphohistiocytosis (p-HLH), a genetic disorder characterized by hyperinflammation, is associated with high mortality in pediatric hematology. This study investigates laboratory and imaging risk factors for mortality in p-HLH and its subtypes.MethodsA retrospective analysis (2012-2024) was conducted on 264 pediatric patients with HLH, categorized into p-HLH and secondary HLH (s-HLH). Five laboratory markers and nine imaging findings were compared between groups and across p-HLH subtypes: familial HLH (F-HLH), immunodeficiency-related HLH (I-HLH), and EBV-driven HLH. Mortality risk factors were analyzed.ResultsThe cohort included 264 pediatric patients (median age: 4 years, IQR: 2–7 years, 141 males), with 99 having p-HLH (28 F-HLH, 34 I-HLH, 37 EBV-driven HLH), and 165 having s-HLH (EBV-associated). No significant differences in laboratory parameters were observed between p-HLH and s-HLH. Imaging revealed that p-HLH was associated with less severe ascites, more pronounced hepatomegaly, and greater central nervous system (CNS) involvement than s-HLH. Subgroup analysis showed that F-HLH had more severe CNS involvement, while I-HLH had higher rates of pulmonary complications. Independent mortality risk factors for HLH overall included severe thrombocytopenia (HR = 2.93, 95%CI:1.62-5.30, p < 0.01), CNS involvement (HR = 1.80, 95%CI:1.14-2.84, p = 0.01), and liver/spleen damage (HR = 2.78, 95%CI:1.85-4.18, p < 0.01). For p-HLH, specifically, severe liver/spleen damage (HR = 2.68, 95%CI:1.38-5.21, p < 0.01) and pleural effusion (HR = 3.98, 95%CI:1.20-13.2, p=0.02) were critical factors.ConclusionNo significant differences in mortality risk were found between p-HLH and s-HLH or among p-HLH subtypes. For p-HLH, severe liver/spleen damage and pleural effusion emerged as key mortality predictors.